Mapping the global research landscape of STEAM education: A bibliometric study of interdisciplinary learning approaches - Aldiansyah, Rifki; Paidi, Paidi; Mualimin, Mualimin; Limiansi, Kintan (STKIP Persada Khatulistiwa Sintang, 2026)
STEAM education has become an increasingly prominent focus in formal education, emphasizing the interdisciplinary integration of science, technology, engineering, arts, and mathematics. However, comprehensive studies mapping global research trends and thematic developments in STEAM remain limited. This study aims to analyze global STEAM research trends, identify influential contributors, and examine thematic evolution through bibliometric analysis. The research employed a Systematic Literature Review (SLR) combined with bibliometric analysis of 184 Scopus-indexed articles published between 2015 and October 2025. Data were analyzed using VOS viewer and Bibliometrix to explore publication patterns, collaboration networks, and thematic clusters. The findings indicate a significant growth in publications, particularly from 2022 to 2025, with the United States, China, and Spain as leading contributors. Lavicza, Z., and Johannes Kepler University Linz were identified as the most productive contributors. Thematic analysis revealed key clusters, including project-based learning, creativity, computational thinking, art integration, and maker-centered learning, reflecting a shift toward transdisciplinary approaches. These results highlight the evolving direction of STEAM education and suggest opportunities for future research in local implementation, technology integration, and authentic assessment.